PEG-Functionalized Chitosan: A Biological Macromolecule as a Novel Corrosion Inhibitor - Srivastava V.; Chauhan D.S.; Joshi P.G.; Maruthapandian V.; Sorour A.A.; Quraishi M.A. (My University, 2025)
In the present work, we have synthesized chemically functionalized chitosan via cross-linking with polyethylene glycol (PEG) and used it as a novel green corrosion inhibitor. This is the first study reporting the use of chitosan-PEG (CS-PEG) as corrosion inhibitor for mild steel in 1 M HCl. The study was performed using weight loss method, electrochemical measurements, surface morphology (AFM) and quantum chemical investigation. The maximum corrosion inhibition efficiency of 93.9% was obtained at a concentration of 200 mgL−1. The inhibitor was found to obey Langmuir adsorption isotherm and exhibited both physical and chemical adsorption. Electrochemical impedance spectroscopy (EIS) showed an increase in the polarization resistance which supported the adsorption and inhibition behavior. Tafel data showed a mixed type behavior with cathodic predominance. The data of quantum chemical calculations supported the experimental findings. © 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim